Reproductive biology of the cockfish, callorhinchus callorynchus (Chondrichthyes: Callorhinchidae), in coastal waters of the northern Argentinean sea - Chierichetti, Melisa Antonela (2017)
The cockfish, Callorhinchus callorynchus, is a widely distributed holocephalan in the south-western Atlantic and an important resource for Argentinean fisheries. The reproductive characteristics of this species were studied in northern Argentinean coastal waters, where specimens arrive seasonally (winter-spring). Sexual dimorphism in maximum precaudal length (PCL) and total body mass (TM) was found, being females (PCL=630 mm; TM=3330 g; n=167) larger and heavier than males (PCL=482 mm; TM=1630 g; n=19). Maturity size for females was 466.22 mm PCL, representing 74% PCL of the largest female sampled. The mean number of ovarian follicles was 8.37 (± 4.84). The highest values of ovarian follicles diameter, gonadosomatic and oviducalsomatic indices were found in spring. A high proportion of mature females (44%) had atretic ovarian follicles, suggesting that they were in the resting stage of their reproductive cycle. The low number of mature males recorded and the absence of mature females with spermatophore masses or egg cases indicate that the study area would not be a reproductive zone. The seasonal presence of C. callorynchus in this region could be related to trophic movements. These results, obtained in an area with high fishing pressure on chondrichthyans, will be useful for implementing conservation and management measures.